Origin and Diversification of South American Polyploid Silene Sect. Physolychnis (Caryophyllaceae) in the Andes and Patagonia - Frajman, Božo; Schönswetter, Peter; Weiss-Schneeweiss, Hanna; Oxelman, Bengt (Frontiers in Genetics, 2018)
The Andes are an important biogeographic region in South America extending for about 8000 km from Venezuela to Argentina. They are – along with the Patagonian steppes – the main distribution area of ca. 18 polyploid species of Silene sect. Physolychnis. Using nuclear ITS and plastid psbE-petG and matK sequences, flow cytometric ploidy level estimations and chromosome counts, and including 13 South American species, we explored the origin and diversification of this group. Our data suggest a single, late Pliocene or early Pleistocene migration of the North American S. verecunda lineage to South America, which was followed by dispersal and diversification of this tetraploid lineage in the Andes, other Argentinian mountain ranges and the Patagonian steppes. Later in the Pleistocene South American populations hybridised with the S. uralensis lineage, which led to allopolyploidisation and origin of decaploid S. chilensis and S. echegarayi occurring at high elevations. Additionally, we show that the morphological differentiation in leaf shape correlated with divergent habitats (high elevation Andes vs. lower elevation Patagonian steppes) is also supported phylogenetically, especially in the ITS tree. Lastly, the species boundaries among the narrow-leaved Patagonian steppe species are poorly resolved and need more thorough taxonomic revision.